1994
DOI: 10.1111/j.1540-8159.1994.tb01417.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Efficacy and Chronic Follow‐Up of Patients with Non‐Thoracotomy Third Generation Implantahle Defibrillators

Abstract: Non-thoracotomy implantation of implantable cardioverter defibrillators (ICDs) has simplified the process of device insertion, promising to decrease associated procedural complications while providing sudden death protection at least equal to epicardial systems. This study presents the acute and chronic results of 110 patients who underwent attempted non-thoracotomy ICD implantation with the Medtronic Transvene lead system and PCD model 7217 or 7219. Of the 110 patients attempted, 100 (91%) had the system succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
4

Year Published

1996
1996
2003
2003

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 8 publications
0
1
0
4
Order By: Relevance
“…(4,17). Die Implantation eines Kardioverter/Defibrillators stellt aber einen invasiven Eingriff mit potentiellen Risiken fŸr den Patienten dar und erfordert besondere operative Voraussetzungen sowie eine sorgfŠltige Nachsorge.…”
Section: Lead-related Complications In 340 Patients With An Implantabunclassified
“…(4,17). Die Implantation eines Kardioverter/Defibrillators stellt aber einen invasiven Eingriff mit potentiellen Risiken fŸr den Patienten dar und erfordert besondere operative Voraussetzungen sowie eine sorgfŠltige Nachsorge.…”
Section: Lead-related Complications In 340 Patients With An Implantabunclassified
“…Multiple studies have shown that implantable cardioverter defibrillators (ICDs) reduce sudden cardiac death in high risk patients who present with sustained ventricular arrhythmias, 1–20 and the majority of these patients will receive the first defibrillator shock within the first 6 to 7 months following implantation 6 , 16 , 21,22 . Most patients presenting with sustained ventricular arrhythmias will eventually receive appropriate defibrillator shock therapy, with the cumulative incidence of appropriate therapy of 13%‐47% after 1 year, and 63%‐80% after 4 to 5 years in high risk patients 7 , 13 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…B. durch Lagewechsel und/oder Armbewegungen provoziert werden können (13). Probleme und Komplikationen des Elektrodensystems sind nicht selten und werden in 5-10% der Patienten beobachtet.…”
Section: Schrittmacherinduzierte Tachykardie (Pmt)unclassified